Implementasi Algoritma First Come First Served dengan Metode Agile pada Sistem Manajement Bengkel Selbaf - Basunondro, Wibiartono; Maimunah; Pristi Sukmasetya (Teknik Informatika Universitas Pamulang, 2024)
This research aims to enhance the efficiency of management at Bengkel Selbaf, a motorcycle injection specialist workshop located in Kuncen, Badran, Kranggan, Temanggung, Central Java. Currently, the workshop relies on manual processes for ordering, scheduling home services, and managing finances and bookkeeping, leading to confusion and difficulties in registration, service queues, and data processing. To address these issues, this study employs the Agile Software Development method to design and develop a web-based application that facilitates workshop management. Data collection techniques used include observation, interviews, and literature review. The result of this research is a